Protein p53 in non-small lung carcinomas - Wyrobiec, Grzegorz; Rokicki, Wojciech; Stęplewska, Katarzyna; Kasperczyk, Janusz; Stępień-Wyrobiec, Olga; Sabat, Daniel; Helewski, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background: Defects in the control of the cellular cycle are one of the major causes of carcinogenesis. Genes and protein p53 take significant in the elimination of impaired cells, through the path of apoptosis. In the mutation of the gene p53 abnormal protein p53 is created. In has longer time of partial decomposition, which causes its accumulation in cells. This protein can be disclosed using the immunohistochemical method. It assumed that accumulation of the protein p53 in cacancerous cells (including the case of non-small cell lung cancer) can be of prognostic significance. Aim : The goal of this thesis is an attmpt of finding some relation between the number of cells accumulating the protein p53, the histological type of non-small cell lung cancer and the size of tumor. Furthermore, the thesis presents the influence of the age of patients operated for the non-small cell lung cancer. Material and methods: The resaarch material consisted of samples of tumours excised during thoracosurgical operations. The research included a group of 94 patients who were operated on due to primary non-small lung carcionoma in the Chest SurgeryClinic of the Medical University of Silesia in Katowice, the Medical Faculty in Zabrze. The methods used in the research were typical immunohistochemical staining techniques using monoclonal antibodies by the Novocastra company: p53 Protein (BP53-12). Results : The biggest number of cells which accumlate protein p53 has been disclosed in the cells of adenocarcinoma whereas the smallest number of cells which accumulate protein p53 has been disclosed in multicellular types of cancer, smaller number of cells accumulating protein p53 has been disclosed in cases of older patients.